2015
DOI: 10.3906/tar-1406-88
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of decomposed leaf litter from intercropped trees on rape

Abstract: The allelopathic effect of decomposed litter from trees interplanted with crops is a key problem in the intercrop agroforestry business that could influence the economic benefits and sustainable development of ecoagriculture. In our study, the litter from 12 common intercropped tree species was collected from the Guanzhong Plain (Shaanxi Province, China) and mixed with soil, incubated to allow decomposition for 120 days, and then extracted using water. The water extracts at different concentrations were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…However, soil temperature and radiation were not the major factors regulating seedling recruitment in this study. Furthermore, study has evident that plant litter addition had direct negative effects on seedling recruitment by allelopathy (Ruprecht et al, ; Zhang et al, ) and mechanical interference (Li & Ma, ; Li, Jia, Long, & Zerbe, ; Mitschunas, Filser, & Wagner, ). These effects may be the main reason for litter addition can directly and significantly inhibit seedling recruitment in this study (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…However, soil temperature and radiation were not the major factors regulating seedling recruitment in this study. Furthermore, study has evident that plant litter addition had direct negative effects on seedling recruitment by allelopathy (Ruprecht et al, ; Zhang et al, ) and mechanical interference (Li & Ma, ; Li, Jia, Long, & Zerbe, ; Mitschunas, Filser, & Wagner, ). These effects may be the main reason for litter addition can directly and significantly inhibit seedling recruitment in this study (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathy has been considered to play a vital role in successful invasions by alien species [8][9]. Certain plant species secrete allelochemicals, which exert positive or negative effects on neighboring plants or microorganisms in the environment [10]. The allelochemical isolated from Ficus microcarpa inhibits the growth of Chlorella pyrenoidosa and the primary active fraction was identified as 2-propyl phenol [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in this study, the humus soil from C. korshinskii inhibited the seed germination of Glycyrrhiza uralensis, which is not in line with the findings of Sun et al (2008), who reported that C. korshinskii roots leaf water extract caused significantly inhibition on the seed germination of Glycyrrhiza uralensis. Based on these differences it shows that the allelochemicals obtained from different sources (living leave water extract/ soil) were different, because allelochemicals may be decomposed or transformed in the soil, which resulted in altering the activities or structure of allelochemicals (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mixture of 5 ml of supernatant liquor and 5 ml of hydrogen peroxid was incubated in a 20°C water bath for 5 min, at the same time add 5 ml sulfuric acid to steady all the undecomposed of hydrogen peroxide, then added 1 ml potassium iodide, 3 drops of ammonium molybdate and 5 drops of starch indicator, at last titrated with a 0.01 mol L -1 sodium thiosulfate solution until the blue disappeared. (Gao, 2000;Chi, 2011;Zhang et al, 2015).…”
Section: Determination Of Physicochemical Indicesmentioning
confidence: 99%
See 1 more Smart Citation